PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (kasus bagian oprasional PT. Indah Logistik Cargon Cabang pekanbaru) - Rosalina Rosalina; Tri Septiana; Vicky F Sanjaya (Indonesian Journal of Thousand Literacies, 2023)
Discipline is the most important function of human resource management and the realization of the main goal because without discipline it is equally difficult to achieve maximum goals. The source of success of an enterprise in producing a high-performance workforce is qualified and has adequate work effectiveness. What is included in the work discipline in this study is punctuality, compliance with regulations, and the ability to maintain office equipment. Performance is the result of work that a person achieves in accordance with the requirements of the job. The results of the quality and quantity of performance achieved by the employee in carrying out his duties in accordance with the responsibilities assigned to him. The factors that affect performance are ability and motivasi.PT. Indah Logistik Cargo Pekanbaru branch is one of the service companies engaged in delivery services. The operational part is the most important part of the company, where the operational part interacts directly with consumers in serving service delivery, and in the operational part, employees who have high ability and motivation are needed to carry out their work and meet their goals. Based on the analysis of this study, it shows that there is a strong influence between work discipline and the performance of employees in the operational department of PT. Indah Logistics Cargo Pekanbaru branch. This can be seen from the analysis of known data from t count (13.637) > t table (1.997) and Sig (0.000) < 0.05. Then the hypothesis of no influence of labor discipline on the performance of employees is accepted